The content of vocational rehabilitation programs for people with special needs between theory and reality - Abaidia, Ahlam (Journal of Human Sciences, 2022)
The study aims to find out whether the educational and training content of vocational rehabilitation programs for people with special needs is adapted to the characteristics of disabled people, through the opinions of specialized trainers, each in their own field, and trainees from people with disabilities who are enrolled in vocational training centers for people with special needs, where the problem of study is concentrated To answer the following questions: The educational and training content of vocational rehabilitation programs for people with special needs special matches the characteristics of people with disabilities? Are there differences in the responses of trainers and trainees on whether the educational and training content of vocational rehabilitation programs for people with special needs are characteristics of the disabled? The study concluded that both trainers and trainees confirm that the educational and training content of special-needs vocational rehabilitation programs is tailored to the characteristics of people with disabilities, and the study also revealed that there are differences between the answers of the trainers and the answers of the trainees. Trainers were noticed to respond to axis sentences in a certain way. Different from trainees on the adequacy of the content of vocational rehabilitation programs to the particularities of disabled people